Singapore Airlines 2001 (A) - Allampalli, D. G. (2013)
The case describes how Singapore Airlines (SIA) evolved from a fledging player in the 1960s into an industry leader in the airline industry. In the process, SIA rewrote the rules for competition and earned accolades for its excellent aviation record, young fleet of planes and a reputation for delighting customers. Bilateral air service agreements negotiated between individual nations limited the routes of a given airline and hence the airline's growth. The global airline industry had responded to this challenge with a mix of acquisition, strategic alliances (for e.g., the STAR alliance) and related diversification strategies. But would these strategies be sustainable in the near future? What course of action should SIA undertake?